Seroprevalence and risk factors for Neospora caninum infection in cattle from the eastern Antioquia, Colombia (2018)
ABSTRACT: Bovine neosporosis is a parasitic disease with worldwide distribution that causes important economic losses. Because of the limited information on the occurrence of Neospora caninum infection in Colombia, this study aimed to determine the seroprevalence and identify the risk factors associated with this infection in cattle in Antioquia, which is the largest milk-producing state in the country. We collected 1,038 blood samples from Holstein, Jersey and crossbred cows from 31 farms. An epidemiologic questionnaire was given to all the owners. A commercial ELISA kit was used as the diagnostic technique. The occurrence of anti-N. caninum antibodies was determined to be 28.3% (294/1038), and 100% of the screened farms were positive, indicating that all the properties had at least one positive animal. The seropositivity within each farm ranged from 5.5% to 50%. A multivariable logistic regression model identified the following as significant risk factors: history of abortion (OR=5.33, p<0.001), replacement with cattle purchased outside the farm (OR=1.54, p<0.05), age (OR=1.7, p<0.01) and poor hygienic practices associated with manual milking (OR=1.69, p<0.01). The latter two factors suggest that horizontal transmission is an important route of infection. This study is the first to report the seroprevalence of and risk factors for N. caninum infection in Antioquia and allows us to conclude that N. caninum is widely distributed in this region.